The Utilization of Red Dragon Fruit Peel Extract (Hylocereus costaricencis) As A Natural Colorant of Dried Noodle - Silaturahmi Silaturahmi; Zaidiyah Zaidiyah; Tengku Mia Rahmiati (Serambi Journal of Agricultural Technology, 2020)
The use of colorants in the dried noodle manufactures is an effort of product diversification. Besides of being used as a natural coloring agent, this peel extract is also used to improve nutritional value of the expected product. The purpose of this study was to determine the effect of red dragon fruit peel extract on the physical quality of dried noodle.  The study was conducted by using Completely Randomized Design (CRD) method with one factor, namely concentration of red dragon fruit peel extract (N1 = 10 ml, N2 = 15 ml, N3 = 20 ml, N4 = 25 ml, N5 = 30 ml).  The observations of its physical quality consisted of water absorption, solid loss during cooking, and organoleptic tests (aroma and color).  The best quality of dried noodle was obtained by using 30 ml red dragon fruit peel extract (N5) with physical properties, namely DSA levels of 351.92%, solid loss during cooking 4.78%, aroma 3.79 (like) and color 3.89 (like).